Association of Eviction With Adverse Birth Outcomes Among Women in Georgia, 2000 to 2016. Issue 11 (November 2021) - Himmelstein, Gracie; Desmond, Matthew
Abstract : (Abstracted from JAMA Pediatr 2021;175(5):494–500) Median US rent has more than doubled in the past 2 decades, which has led to an increase in eviction rates. Eviction has been associated with numerous adverse health outcomes.